HEAD PEDICULOSIS AMONG IN BAGHDAD AREA ELEMENTARY SCHOOLCHILDREN - Mahmood, Shayma (Iraqi Journal of Science, 2024)
Head louse is an integumentary disease infesting human hair and caused by the ectoparasite Pediculus humanus capitis. The endimicity of the disease among Iraqi elementary schoolchildren was investigated during the period from January to May 2009 in the city of Baghdad. From eight elementary schools, 540 boys and girls were included in the study. The total rate of infestation was 13.5%, however this rate was significantly higher among girls (17.33%) comparing to boys (8.75%). The prevalence rate was found to be highly influenced by certain factors. These were including the age (the rate was significantly higher (18.7%) among the age group of >8-10 years compared to other age groups), the hair characters (the rate was significantly higher (14.35-22.2%) among the black, straight long hairs compared to other hair characters groups), the crowdness of the classrooms (the highest rate was noticed among children in highly crowded (15.7%) compared to non-crowded classrooms) and the socioeconomic standards of the children’s families (the highest rates (22-26.7%) were reported among children with different degrees of low economical, social and educational levels).